Vulnerability mapping of 100 priority tree species in Central Africa to guide conservation and restoration efforts - Ceccarelli, Viviana; Ekue, Marius; Fremout, Tobias; Gaisberger, Hannes; Kettle, Christopher J.; Taedoumg, Hermann; Wouters, Hendrik; Vanuytrecht, Eline; Ridder, Koen de; Thomas, Evert (Elsevier, 2022)
Climate change and other anthropogenic threats are increasingly imperilling the diverse biomes of Central Africa, which are globally important for biodiversity, carbon storage and people's livelihoods. The objectives of this paper were to: (i) map the vulnerability of 100 socio-ecologically important priority tree species in Central Africa to climate change, fire, habitat conversion, overexploitation, overgrazing and (ii) propose a spatially explicit strategy to guide restoration and conservation actions. We performed ensemble distribution modelling to predict the present and future distributions of the 100 species, assembled other anthropogenic threat exposure layers, assessed species' sensitivities to the five threats based on their trait profiles, and constructed species-specific vulnerability maps by combining the species' exposure and sensitivity. The results show that these 100 species are vulnerable to the five threats, with an average of 34% of their distribution ranges under high to very high vulnerability and 60% under medium to high vulnerability to at least one threat. Many species identified as most vulnerable in this study are not considered as threatened by the IUCN Red List, suggesting a need to update their conservation status, potentially through integration of the vulnerability mapping methodology we used here. We generated both species-specific maps and summary maps including all 100 species identifying priority areas for a) in-situ conservation, b) ex-situ conservation, and c) active planting or assisted natural regeneration. We present an online platform to enable easy access to the vulnerability and the conservation and restoration priority maps for decision makers and support conservation and restoration planning across Central Africa.